The Evolving Importance of Banks and Securities Markets - Demirgüç-Kunt, Asli; Feyen, Erik; Levine, Ross (Oxford University Press on behalf of the World Bank, 2015)
The roles of banks and securities markets evolve during the process of economic development. As countries develop economically, (1) the size of both banks and securities markets increases relative to the size of the economy, (2) the association between an increase in economic output and an increase in bank development becomes smaller, and (3) the association between an increase in economic output and an increase in securities market development becomes larger. These findings are consistent with theories predicting that as economies develop, the services provided by securities markets become more important for economic activity, whereas those provided by banks become less important.